Influence of the Upper Limb Motor Deficit on Functional Independence in Patients with Cerebral Palsy - Corina SPOREA; Dumitru FERECHIDE (Modern Medicine)
Cerebral palsies (CPs) disturb the voluntary movement control at extremities’ level, entailing various disability degrees. In over 80% of the CP cases there is an upper limb disorder, mainly manifested by the decrease in hand control and the presence of contractures, which, in time, lead to the adoption of abnormal postures which affect the abilities of the CP patients’ hands. The aim of this study was to identify the way the motor deficit at upper limb level – reflected by coordination disturbances and by the condition of the three fingered (tripod) grasp – influences the CP patient’s functional independence. The study demonstrated the existence of significant correlations between Functional Independence Measure (FIM) score, coordination and three fingered grasp. It was proven that the unilateral coordination dysfunctions have a strong negative influence on the coordination of the opposite side and lead to a decrease of the functional independence level. Therefore, the rehabilitation treatment is recommended to be based on a bilateral training, both in order to improve coordination and to obtain a functional level of the three fingered grasp power and of the physiological amplitude at wrist flexion level.